Physiotherapy in Ophthalmology – a Literature Review - Elżbieta Szczygieł; Natalia Fudacz; Tomasz Berus; Jagoda Rojek; Edward Golec (Rehabilitacja Medyczna)
Introduction: Eye disease or visual impairment, such as myopia and hyperopia, is now a common problem. Various types of vision therapy and eye exercises are available.Objective: To estimate publications assessing the impact of various eye exercises on visual parameters in order to determine their effectiveness in the treatment and prevention of visual impairment.Data sources: Ebsco, PubMed and Medline were searched between April 10-15, 2021.Study selection: The study comprised a controlled trial, randomised clinical trial, case control study, nested case-control study and comparative study in which the effects were examined of eye therapy or eye exercise among adults, adolescents and children with refractive eye errors or regular eyes.Data extraction and synthesis: The analysis was based on the PRISMA recommendations (Preferred Reporting Items for Systematic Review and Meta-Analysis).Results: Nineteen publications were analysed in detail. Considering visual parameters, the largest number of studies (16 articles) concerned refractive defects of the eye, such as myopia or hyperopia. Various interventions were used, the most popular being the Bates method (8 articles), eye yoga exercise (7 articles), Chinese eye exercises and vision therapy (1 article). The most commonly used eye assessment tools were the autorefractometer (4 articles) and Snellen’s chart (6 articles).Conclusions: Eye exercises have a positive effect on the treatment of myopia and improve binocular vision.